Communication and dissemination of vernacular heritage - Correia, Mariana (2022)
Vernacular architecture is one of the most significant cultural expressions of a socio-economic structure: it represents the way in which local materials and traditional building techniques, learned from endogenous evolutionary processes and from cultural advances, were used to respond to the physical and socio-economic needs of a group, thus generating remarkable architectural models adapted to the historical-cultural experience and the specific environmental restriction of each territory. They are, therefore, unique models strongly linked both to the environmental and to the socio-economic and cultural context, which nevertheless have universal elements in common: they use local resources; they adapt strongly to the morphology and to the bioclimatic characteristics of the place; they are the result of the transmission of experience and knowledge; they are the expression of a living model and the identity of a group; they are extremely vulnerable, as they face sudden changes (natural or cultural); and the deterioration process can be easily triggered.